Adoption of Digital Services by Muslim Communities in Central Java (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
Adopting digital services is a logical consequence of welcoming the digital era, but in-depth studies on digital services still need to be completed. This quantitative research aims to determine the effect of relative advantage, compatibility, and complexity technology on adopting digital services in Muslim communities in Central Java. The sample of this study is the Muslim community and users of digital services in Central Java, selected by incidental sampling techniques. Multiple linear regression analysis tools were used with the help of SPSS software to test the effect of independent variables with dependents. The results prove that relative advantage, compatibility, and complexity significantly positively affect the adoption of services.